CORRELATION BETWEEN THE INITIAL-SURGERY AGE WITH THE HIRSCHSPRUNG’S DISEASE PATIENT STOOLING PATTERNS IN ULIN HOSPITAL BANJARMASIN, SOUTH KALIMANTAN, INDONESIA IN 2012-2015 - Elvira Esmeralda Poerwosusanta; IGB Adria Hariastawa; Ariandi Setiawan; Sulistiawati Sulistiawati; Agung Ary Wibowo (Universitas Airlangga, Surabaya, Indonesia, 2021)
Background: Hirschsprung's disease may lead to gastrointestinal obstruction if not appropriately treated. The initial-surgery or colostomy is intended to decompress the large bowel, prevent enterocolitis, and the stooling-patterns can be measured after definitive surgery. Objective: To determine the correlation between initial-surgery age with stooling-patterns. Materials and Methods: We performed an analytic observational study in Ulin Hospital in Banjarmasin, South Kalimantan, Indonesia, from November to December 2015 with a total sample of 31 patients. The initial-surgery age was divided into before and after 30 days, while the stooling-patterns were divided into satisfied and not satisfied. Results: There was no significant correlation between initial-surgery age with stooling patterns. Most of the patients, 18/31 (58.1%), underwent initial-surgery after 30 days, and 23/31 (74.2%) had satisfied stooling patterns after surgery. Conclusion: No significant correlation between initial-surgery age and stooling patterns among Hirschsprung's disease patients.